Методичні засади дослідження кадрового потенціалу вищого навчального закладу - Тугай, А. М.; Гойко, А. Ф.; Єлішевич, М. А.; Криштоф, С. Д.; Воронюк, О. І. (Ways to Improve Construction Efficiency, 2013)
Disclosed the concept of the category "human potential" of the university, methodical basis of his research, as well as basic principles, objectives and operational measures of the human resources policy at the present stage.